Pengaruh Promosi Dan Kualitas Produk Oppo Terhadap Minat Beli Konsumen - Donovan, Donovan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This study aims to determine the influence of promotion and product quality of Oppo on consumer buying interest. This research method uses quantitative methods with probability sampling techniques or random sampling of 100 people using gadgets. Instrument testing is carried out by testing the validity and reliability tests. The method of data analysis was carried out using descriptive statistical tests and hypothesis testing (multiple linear regression analysis). The results of the research show that promotion has a significant effect and product quality has a significant influence on consumer buying interest. The conclusion of this study is that both promotion and quality have significant results on purchasing decisions.